Difluorenyl carbo‐Benzenes: Synthesis, Electronic Structure, and Two‐Photon Absorption Properties of Hydrocarbon Quadrupolar Chromophores. Issue 40 (12th August 2015) - Baglai , Iaroslav; de Anda‐Villa, Manuel; Barba‐Barba, Rodrigo M.; Poidevin, Corentin; Ramos‐Ortíz, Gabriel; Maraval , Valérie; Lepetit , Christine; Saffon‐Merceron, Nathalie; Maldonado, José‐Luis; Chauvin , Remi
Abstract: The synthesis, crystal and electronic structures, and one‐ and two‐photon absorption properties of two quadrupolar fluorenyl‐substituted tetraphenyl carbo ‐benzenes are described. These all‐hydrocarbon chromophores, differing in the nature of the linkers between the fluorenyl substituents and the carbo ‐benzene core (CC bonds for3 a, CCCC expanders for3 b ), exhibit quasi–superimposable one‐photon absorption (1PA) spectra but different two‐photon absorption (2PA) cross‐sections σ 2PA . Z ‐scan measurements (under NIR femtosecond excitation) indeed showed that the CC expansion results in an approximately twofold increase in the σ 2PA value, from 336 to 656 GM (1 GM=10 −50  cm 4  s molecule −1  photon −1 ) at λ =800 nm. The first excited states of Au and Ag symmetry accounting for 1PA and 2PA, respectively, were calculated at the TDDFT level of theory and used for sum‐over‐state estimations of σ 2PA ( λi ), in which λi =2  hc / Ei, h is Planck's constant, c is the speed of light, and Ei is the energy of the 2PA‐allowed transition. The calculated σ 2PA values of 227 GM at 687 nm for3 a and 349 GM at 708 nm for3 b are in agreement with the Z ‐scan results. Abstract : carbo ‐Chromophores : The synthesis, crystal and electronic structures, and one‐ and two‐photon absorption properties of two quadrupolar fluorenyl‐substituted tetraphenyl carbo ‐benzenes are described. These all‐hydrocarbon chromophores, which differ in the nature of the linkers between the fluorenyl substituents and the carbo ‐benzene core (CC bonds or CCCC expanders), exhibit quasi‐superimposable one‐photon absorption spectra but different two‐photon absorption cross‐sections σ 2PA (see figure).